Hermeneutyka słowa Bożego w liturgii - Dyk, Stanisław (Studia Pastoralne, 2026)
Bible and liturgy as sacred texts are basic, although not the only ones, sources of homilies. These sources should be analysed as closely related with one another. Homily, mystagogic in its nature and function, is preaching the mystery of Christ revealed in the Holy Scripture and celebrated in the liturgy. For in „here and now” of the liturgy redemptive events revealed in the Bible are being actualised. To a considerable extent the Bible was written for liturgical purposes. Therefore liturgy is the major exegetic place of the Holy Scripture. A preacher interpreting holy texts should be aware of this mutual intertwining of the Bible and liturgy. Liturgical hermeneutics of the Word of God takes into consideration both a sense and functions of biblical texts within liturgy. To achieve this aim the content of the Bible is compared to the meaning of other biblical texts, euchological texts as well as the meaning of signs and liturgical symbols. The Word of God in liturgy, however, is interpreted above all in the light of the mystery of Christ celebrated in the cult. The redemptive mystery itself receives, on the other hand, deeper light and understanding from the proclaimed Word of God. Hermeneutical technique analyses as well the way biblical texts are distributed within a liturgical year. Attention is drawn on this occasion to the rules of interpretation of the Word of God in liturgy, which are as follows: chrystocentrism, dynamics of acts of the Holy Spirit, ecclesiality, particular needs of listeners.